2015
DOI: 10.1186/s12917-015-0347-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyto-adherence of Mycoplasma mycoides subsp. mycoides to bovine lung epithelial cells

Abstract: BackgroundMycoplasma mycoides subsp. mycoides (Mmm) is the causative agent of contagious bovine pleuropneumonia (CBPP), a respiratory disease of cattle, whereas the closely related Mycoplasma mycoides subsp. capri (Mmc) is a goat pathogen. Cyto-adherence is a crucial step in host colonization by mycoplasmas and subsequent pathogenesis. The aim of this study was to investigate the interactions between Mmm and mammalian host cells by establishing a cyto-adherence flow cytometric assay and comparing tissue and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…As reported by Aye et al [55], Mmm is less adherent to endothelial cells than to epithelial cells. Similarly, we did not detect Mmm AfadĂ© adherent to endothelial cells of the blood vessels present in the PCLS and from cattle infected with Mmm AfadĂ© (Data not shown).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As reported by Aye et al [55], Mmm is less adherent to endothelial cells than to epithelial cells. Similarly, we did not detect Mmm AfadĂ© adherent to endothelial cells of the blood vessels present in the PCLS and from cattle infected with Mmm AfadĂ© (Data not shown).…”
Section: Discussionsupporting
confidence: 56%
“…Our result is in agreement with a previous report that Mmm is both species and tissue-specific. Aye and colleagues [55] could show significantly higher numbers of Mmm adherent to adult primary lung epithelial cells compared to primary caprine lung epithelial cells. On the contrary, the adherence of fast-growing Mmc was not strongly influenced by the type of host tissue since we observed a continuous increase in caprine as well as bovine PCLS.…”
Section: Discussionmentioning
confidence: 99%
“…Since CBPP spreads by the respiratory route, non-ciliated epithelial cells residing within bronchioles and alveoli should be regarded as the earliest and most relevant cellular targets of infection. As widely shown for other respiratory pathogens (namely, influenza viruses), the different expression of cellular surface molecules—which might vary with age and/or along the airways—could strongly influence the tropism of Mmm and should be investigated in depth [ 19 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cytoadherence assay and flow cytometry analysis were performed as previously described ( Aye et al, 2015 ). The proportion of cells to which mycoplasmas had bound was calculated using Flow Jo ( FLOWJO, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we established a cytoadherence assay that measured the interaction of Mmm with various host cells and showed that Mmm cytoadherence is tissue and host specific ( Aye et al, 2015 ). In this study we further analyzed the adhesion of Mycoplasma mycoides subspecies mycoides ( Mmm ), the causative agent of contagious bovine pleuropneumonia (CBPP), an important disease of cattle in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%